Rancang Bangun Sistem Monitoring Patroli Lingkungan Kampus Menggunakan Near Field Communication Berbasis Android dan Web Application - Jullia Fatriana Putri; Ahmad Taqwa; Irma Salamah (LPPM UBHINUS MALANG, 2021)
Campus security is a condition that shows that every campus community must feel safe and comfortable. The higher the security level of the campus environment, the lower the risk of loss due to loss of assets or damage to the campus environment. Therefore, a research entitled